108k views
3 votes
Which equation is represented by the model? 3x2 – 4x – 1 = (3x + 1)(x – 1) 3x2 – 2x – 1 = (3x – 1)(x + 1) 3x2 – 4x + 1 = (3x – 1)(x – 1) 3x2 – 2x + 1 = (3x – 1)(x – 1)

2 Answers

4 votes

Answer:

C 3x2 – 4x + 1 = (3x – 1)(x – 1)

Explanation:

User Oligopol
by
4.4k points
4 votes

Answer:

The correct option is 3.

Explanation:

In option 1,

The given equation is


3x^2-4x-1=(3x+1)(x-1)

Simplify the right sides.


3x^2-4x-1=3x(x-1)+1(x-1)


3x^2-4x-1=3x^2-3x+1x-1


3x^2-4x-1 \\eq 3x^2-2x-1

Since left hand side is not equal to right hand side, therefore option 1 is incorrect.

In option 2,

The given equation is


3x^2-2x-1=(3x-1)(x+1)

Simplify the right sides.


3x^2-4x-1\\eq 3x^2+2x-1

Since left hand side is not equal to right hand side, therefore option 2 is incorrect.

In option 3,

The given equation is


3x^2-4x+1=(3x-1)(x-1)

Simplify the right sides.


3x^2-4x+1=3x^2-4x+1

Since left hand side is equal to right hand side, therefore option 3 is correct.

In option 4,

The given equation is


3x^2-2x+1=(3x-1)(x-1)

Simplify the right sides.


3x^2-2x+1\\eq 3x^2-4x+1

Since left hand side it not equal to right hand side, therefore option 4 is incorrect.

User Qoheleth
by
5.0k points